PERILAKU MENYONTEK SISWA DITINJAU DARI JENIS KELAMIN - Musslifah, Anniez Rachmawati (TALENTA, 2015)
ABSTRACTCheating  behavior  is  one  of  the  educational  phenomenon  that  we  often  encounter accompany the learning process. There are various factors that influence the behavior of cheating, one of the factors that influence the behavior of such cheating is sex. This study aims  to  analyze  the  extent  to  which  gender  affects  the  behavior  of  cheating  on  the students.Population in this research is the students of SMAN 1 Widodaren with a sample size of  70  people.  Samples  were  taken  at  random  cluster  sampling  technique.  The  data collection method using a scale behavior of cheating which is then analyzed by Annava one  lane.The  analysis  showed  that  there  was  no  significant  difference  in  terms  of  cheating behavior  in  terms  of  sex  differences  with  F  value  of  2.813  with  p  =  0.094  (p>  0.05). These  results  indicate  that  gender  does  not  affect  the  behavior  of  cheating  on  the students.Keywords: sex, cheating behavio